Cryptorchidism and Testicular Tumor: Comprehensive Analysis of Common Clinical Features and Search of SNVs in the KIT and AR Genes - Landero-Huerta, Daniel Adrian; Vigueras-Villaseñor, Rosa María; Yokoyama-Rebollar, Emiy; García-Andrade, Fabiola; Rojas-Castañeda, Julio César; Herrera-Montalvo, Luis Alonso; Díaz-Chávez, José; Pérez-Añorve, Isidro Xavier; Aréchaga-Ocampo, Elena; Chávez-Saldaña, Margarita Dolores (Frontiers in Cell and Developmental Biology, 2020)
Allelic variants in genes implicated in the development of testicular germ cell tumor (TGCT) could be present in patients with cryptorchidism (CO). Currently; the mechanisms explaining this relationship are still unknown. In this study the common clinical features in patients with CO and TGCT and 6 variants of KIT and AR genes associated to TGCT were analyzed. Population analyzed included 328 individuals: 91 patients with CO; 79 with TGCT, 13 of them with previous CO diagnosis and 158 healthy males. Of the 13 patients with TGCT and history of CO, one patient (7.7%) presented the heterozygous form of the variant rs121913507 and two patients (15.4%) presented homozygote genotype for the variant rs121913506 in KIT gene. Interestingly, the heterozygous form for the variant rs121913506 of KIT gene was identifying in all of 13 patients. The rs201934623, rs774171864 and rs12014709 variants of the AR gene did not show any clinical association. Our results strongly support that genetic component in CO could be conditioning for the development of TGCT. Notably, KIT gene variants might be determinants in the pathological association between TGCT and CO.